Appropriate Thiamin Pyrophosphate Levels Are Required for Acclimation to Changes in Photoperiod - Rosado-Souza, Laise (Plant Physiol, 2019)
Thiamin pyrophosphate (TPP) is the active form of vitamin B(1) and works as an essential cofactor for enzymes in key metabolic pathways, such as the tricarboxylic acid (TCA) cycle and the pentose phosphate pathway. Although its action as a coenzyme has been well documented, the roles of TPP in plant metabolism are still not fully understood. Here, we investigated the functions of TPP in the regulation of the metabolic networks during photoperiod transition using previously described Arabidopsis (Arabidopsis thaliana) riboswitch mutant plants, which accumulate thiamin vitamers. The results show that photosynthetic and metabolic phenotypes of TPP riboswitch mutants are photoperiod dependent. Additionally, the mutants are more distinct from control plants when plants are transferred from a short-day to a long-day photoperiod, suggesting that TPP also plays a role in metabolic acclimation to the photoperiod. Control plants showed changes in the amplitude of diurnal oscillation in the levels of metabolites, including glycine, maltose, and fumarate, following the photoperiod transition. Interestingly, many of these changes are not present in TPP riboswitch mutant plants, demonstrating their lack of metabolic flexibility. Our results also indicate a close relationship between photorespiration and the TCA cycle, as TPP riboswitch mutants accumulate less photorespiratory intermediates. This study shows the potential role of vitamin B(1) in the diurnal regulation of central carbon metabolism in plants and the importance of maintaining appropriate cellular levels of thiamin vitamers for the plant’s metabolic flexibility and ability to acclimate to an altered photoperiod.